Planning a family in Nairobi's informal settlements: results of a qualitative study. Issue 2 (8th March 2020) - Towriss, Catriona A.; Beguy, Donatien; Wringe, Alison; Hussein, Barwako Hassan; Timæus, Ian M.
Abstract: Childbearing intentions among women in high-fertility contexts are usually classified into those wanting to have a baby, those wanting to 'space' a birth and those wanting to 'limit' their family size. However, evidence from Africa increasingly suggests that women's intentions are more complex than this classification suggests, and that there is fluidity in these intentions. This research explores women's accounts of their childbearing intentions and decisions in order to examine how this fluidity plays out in a low-fertility context in urban Africa. Six focus group discussions were conducted in April and May 2012 with women of reproductive age in Nairobi, Kenya. Participants were recruited using random and purposive sampling techniques. The focus group discussions had an average of seven participants each. Data were coded thematically and analysed using Nvivo software. The analysis explored the factors that women consider to be influential for childbearing and found that the health of the mother and child, costs of raising a child and relationships were commonly reported to be important. Evidence of intentions to space births and limit family size was found. However, the data also showed that there is fluidity in women's family planning intentions, driven by changes in relationships or household finances, which often result in a desire to avoid pregnancy in the present moment. The fluidity observed in women's childbearing intentions cannot be accounted for by the concepts of either 'spacing' or 'limitation' but is best explained by the concept of 'postponement'. The research reveals the need for family planning clinics to provide a full method mix, as well as high-quality counselling, to enable women to choose a method that best suits their needs.